+0  
 
0
926
1
avatar
Por favor como es
2 (((x-3)+5x)-(2x-3)) = 10-(x-8)
se los pido por favor.
 30 oct. 2013

Mejor Respuesta  

 #1
avatar+111541 
+3
2 (((x-3)+5x)-(2x-3)) = 10-(x-8)

2((x-3+5x) - 1(2x-3) = 10-1(x-8)

2(6x-3 -2x+3) = 10-x+8

2(4x) = 18-x

8x = 18-x

9x = 18

x=2
 30 oct. 2013
 #1
avatar+111541 
+3
Mejor Respuesta 2 (((x-3)+5x)-(2x-3)) = 10-(x-8)

2((x-3+5x) - 1(2x-3) = 10-1(x-8)

2(6x-3 -2x+3) = 10-x+8

2(4x) = 18-x

8x = 18-x

9x = 18

x=2
Melody 30 oct. 2013

11 Usuarios en línea